UPAYA PERLINDUNGAN HUKUM PADA KONSUMEN DALAM TRANSAKSI E-COMMERCE - Munazar Umar (Jurnal Cakrawala Ilmiah, 2024)
The swift advancement of information technology has changed how transactions are conducted through e-commerce, bringing both advantages and new challenges concerning consumer protection. In these transactions, consumers often find themselves in a precarious position, dealing with issues like uncertainty about product quality, shipping delays, and threats to the security of their personal data. Implementing legal safeguards that cover transaction security, transparency of product information, and mechanisms for dispute resolution is crucial. In Indonesia, Law No. 8 of 1999 on Consumer Protection and Government Regulation No. 80 of 2019 provide the legal framework; however, these regulations still face implementation challenges. Consequently, it is essential for the government, businesses, and consumers to collaborate and enhance education to increase awareness of consumer rights. Furthermore, technology plays a vital role in establishing a secure and transparent e-commerce environment.